Efek Tegangan Searah pada Aliran Ionik dan Geometri Pelepah dan Daun Kelapa Sawit - Toto Saktioto; Defrianto Defrianto; Suhardi Suhardi; Dewi Indriyani Roslim; Awitdrus Awitdrus (PERTETA, 2018)
AbstractProductivity of palm tree grown are generally measured in months periods, but in a shorter time scale is particularly less measured by the plant maintenance of palm tree. Consideration of the general productivity in time is how to produce good fruit fertilizer (chemical aspect), healthy plants, fast growing and evolving (agricultural aspect) and genetic type of palm that grows (biological aspect). However, the growth and production on the physical aspect is still less attention. Through physical treatment, the growth of palm tree can be optimized, as it has been proven in advanced countries on the plant Aloe Vera, Avocado and Pine trees. This paper proposes a treatment of direct current voltage to palm tree that can accelerate the flow of ions to grow and develop nutrients with the increment of geometry and sturcture of leaf and midrib. The palm tree samples are aged 1 to 5 years corresponding to the provision of various current voltage. Identification of samples before and after treatment by electricity determined is based on the geometry of leaves and midrib and ions effect. This identification can support the productivity of palm trees.AbstrakProduktivitas kelapa sawit pada umumnya diukur dalam periode bulanan, tetapi dalam skala waktu yang lebih singkat masih kurang terukur dengan pemeliharaan tanaman sawit. Pertimbangan umum produktivitas tersebut adalah bagaimana pupuk menghasilkan buah yang baik (aspek kimia), tanaman sehat, cepat tumbuh dan berkembang (aspek pertanian), dan jenis genetik sawit yang tumbuh (aspek biologi). Namun, pertumbuhan dan produksi pada aspek fisik masih kurang diperhatikan. Melalui perlakuan fisis, pertumbuhan kelapa sawit dapat dioptimalkan, seperti yang telah teruji di negara-negara maju pada tanaman Aloe Vera, Avocado dan Pohon Pinus. Perlakuan pemberian tegangan listrik searah terhadapkelapa sawit dapat memepercepat aliran ion-ion untuk tumbuh dan berkembang dengan penambahan unsur hara dan struktur geometri pada daun dan pelepah. Sampel yang digunakan adalah pohon sawitberusia 1 hingga 5 tahun dengan pemberian tegangan bervariasi. Identifikasi sampel sebelum dan setelah diberi perlakuan listrik ditentukan berdasarkan geometri daun dan pelepah dan efek ion-ion. Identifikasi ini dapat mendukung produktivitas tanaman sawit.